Fuzzy multi-objective programming model for logistics service supplier selection - Rui Ding; Yan Chen; Lin He (2009 Chinese Control and Decision Conference, 2009)
A fuzzy multi-objective integer programming model is developed in this paper for solving the logistics service selection problem with multiple objectives, in which some of the parameters are fuzzy in nature. And an asymmetric fuzzy-decision making technique is applied to enable the decision-maker to assign different weights to various criteria. An application example was also given to testify the feasibility and effectiveness of the proposed method.